Insufficient choline intake during pregnancy: cohort study - GOMES,Caroline de Barros (2021)
ABSTRACT Objective To investigate the intake of choline during pregnancy and associated factors. Methods Cohort study with 353 pregnant women recruited from the primary health care network in an inland city of the State of São Paulo. In-house interviews were conducted in each of the gestational trimesters. In each of these points in time, a 24-hour dietary recall was collected. Subsequently, a new dietary recall collection was performed by telephone in the same trimester on a non-consecutive day, differentiating weekday versus weekend/holiday. Dietary intake data were included in the Nutrition Data System for Research software, and the habitual food intake throughout pregnancy was determined, with intra-individual variation correction in the MSM software. The influence of socioeconomic, obstetric and lifestyle factors, and of the actual diet, on choline intake during pregnancy was assessed using linear regression models, that were developed with the Stata software version 14.2, at a significance level of 95%. Results Choline intake (281.1±68.6 milligrams) was below the recommended adequate intake, and only energy was positively associated with this micronutrient intake. Conclusion Choline intake in the population studied fell far short of current recommendations, and only higher energy intake was found as a factor associated with a higher intake.